Studi Analisis Dokumen Implementasi Kurikulum Merdeka di Sma Negeri 67 Jakarta - Isoh Sukaesah; Rugaiyah; Masduki (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the implementation of the Independent Curriculum through document studies at SMA Negeri 67 Jakarta. The main focus of this study includes planning, learning implementation strategies, monitoring and evaluation systems, as well as obstacles and follow-ups faced in its implementation. The method used is a qualitative approach with data collection techniques in the form of documentation studies and distributing questionnaires to teachers as respondents. The results of the study indicate that the planning for the implementation of the Independent Curriculum at the school has been carried out systematically through the stages of understanding the concept, compiling teaching modules, and internal socialization. The learning implementation strategy is directed at supporting flexibility and differentiation according to student characteristics, as well as the integration of project-based learning in the Pancasila Student Profile Strengthening Project (P5) activities. The monitoring and evaluation system has been running through supervision and observation, but reflective activities such as the P5 showcase are still less than optimal. The main obstacles include differences in teacher understanding, limited facilities, and less than optimal documentation of good practices. The school has responded through internal training, mentoring learning communities, and strengthening the school MGMP. These findings provide an overview that the implementation of the Independent Curriculum in educational units requires collaborative planning, strengthening teacher capacity, and a reflective and sustainable evaluation system.